2012
DOI: 10.1111/j.1600-0404.2012.01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced serum uric acid levels in neuromyelitis optica: serum uric acid levels are reduced during relapses in NMO

Abstract: UA levels are associated with clinical disease status in patients with NMO. Further investigations are recommended to elucidate the role of UA as a biomarker of disease activity in NMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Follow-up liver function tests and routine blood tests revealed immediate liver function damage followed by recovery, consistent with the findings of a study by Chen et al (23). IRE causes significant abnormalities in liver function; however, in the majority of patients these are self-limiting, do not preclude treatment and resemble the changes observed following radiofrequency ablation or cryoablation of the liver (24). IRE for the treatment of liver cancer is associated with hepatocyte destruction and the subsequent release of transaminases and bilirubin, which are considered as important markers of hepatic functional reserve (25).…”
Section: Discussionsupporting
confidence: 89%
“…Follow-up liver function tests and routine blood tests revealed immediate liver function damage followed by recovery, consistent with the findings of a study by Chen et al (23). IRE causes significant abnormalities in liver function; however, in the majority of patients these are self-limiting, do not preclude treatment and resemble the changes observed following radiofrequency ablation or cryoablation of the liver (24). IRE for the treatment of liver cancer is associated with hepatocyte destruction and the subsequent release of transaminases and bilirubin, which are considered as important markers of hepatic functional reserve (25).…”
Section: Discussionsupporting
confidence: 89%
“…In a congenital glaucomatic rabbit model, UA levels in the aqueous humor have been found to be significantly lower compared with age-matched controls (17.1 ± 3.2 and 189.1 ± 75.70 μ M/mg, respectively) [27]. Several studies have also reported that UA levels in patients with neuromyelitis optica were significantly lower compared with healthy control subjects [46, 47]. With the focus more on eyes and their nerves, these findings directly support our results in that subjects with a lower baseline serum UA level have a higher probability of experiencing glaucomatous progression during the follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Min et al. (2012) suggest that serum UA levels decrease in NMO patients during relapse compared with healthy subjects, but then normalize during remission, which suggests that serum UA levels are associated with clinical disease status in NMO patients. In the present paper, CSF UA levels were significantly increased, and serum UA levels were mildly elevated in NMOSD patients during relapse compared with patients with noninflammatory and non‐neurodegenerative diseases, although CSF and serum UA levels were not measured during remission.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is also thought to be involved in NMO and MS (Gonsette, 2008; Haider, 2015; Lassmann & van Horssen, 2016; Penton‐Rol et al., 2009). Previous studies have focused more on serum UA in NMO/MS patients (Ashtari, Bahar, Aghaei, & Zahed, 2013; Liu et al., 2013; Min et al., 2012; Peng et al., 2008; Sotgiu et al., 2002), although cerebrospinal fluid (CSF) UA levels might more directly reflect CNS. However, very little is known about CSF UA levels in NMOSDs.…”
Section: Introductionmentioning
confidence: 99%